Analiza wskaźnikowa a model zarządzania jednostką samorządu terytorialnego - Sierak, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Factor analysis is a very important estimation tool of national budget, financial liability and credibility of local community unit. Range of factor analysis remains in a strict connection with realized in the local community unit management model. In the administration model it is much more limited and has passive character in moulding politics which satisfies current resident needs and indicates development directions. To head for budget programming which includes rational current expenditures and effective investments, the strategic model is applied, in which indicator analysis are very important tools. They are an element of estimation of current financial situation and investment potential in different functional scenarios and development of local community units. Their consistent use should improve management efficiency. Implementation and realization of strategic management model puts local government, administrative and province units in difficult situation. Experiments indicate that in Polish conditions it is very often a crucial barrier to improve the functional efficiency of local community units. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 623-632